2017
DOI: 10.18632/oncotarget.22014
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-141-3p regulates osteoblast activity to promote the osteoblastic metastasis of prostate cancer

Abstract: Exosomes from cancer cells, which contain microRNA and reach metastasis loci prior to cancer cells, stimulate the formation of a metastatic microenvironment. Previous studies have shown that exosomal miR-141-3p is associated with metastatic prostate cancer (PCa). However, the role and regulatory mechanism of miR-141-3p in the microenvironment of bone metastases require further study. In this study, we performed a series of experiments in vivo and in vitro to determine whether exosomal miR-141-3p from MDA PCa 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 53 publications
3
99
1
Order By: Relevance
“…In terms of PCa, there are several studies regarding the potential of serum and urine exosomes as biomarkers (Valentino et al, 2017;Wani et al, 2017;Fujita and Nonomura, 2018;Lee et al, 2018;Panigrahi et al, 2018;Wang et al, 2018); however, there are limited functional studies that delineate if exosomes mechanistically impact PCa metastasis. In one study, exosomes containing miR-141-3p were shown to target osteoblasts and increase osteoblast activity (Ye et al, 2017). Although, the authors concluded in that study that exosome miR-141-3p enhanced osteoblastic metastasis, in that study, they injected mimic miR-141-3p miRNAs into the cancer cells that were then injected into the mice intratibially; thus, one may not conclude that the exosomes achieved their effect through altering the microenvironment or that there was any impact on tumor seeding.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of PCa, there are several studies regarding the potential of serum and urine exosomes as biomarkers (Valentino et al, 2017;Wani et al, 2017;Fujita and Nonomura, 2018;Lee et al, 2018;Panigrahi et al, 2018;Wang et al, 2018); however, there are limited functional studies that delineate if exosomes mechanistically impact PCa metastasis. In one study, exosomes containing miR-141-3p were shown to target osteoblasts and increase osteoblast activity (Ye et al, 2017). Although, the authors concluded in that study that exosome miR-141-3p enhanced osteoblastic metastasis, in that study, they injected mimic miR-141-3p miRNAs into the cancer cells that were then injected into the mice intratibially; thus, one may not conclude that the exosomes achieved their effect through altering the microenvironment or that there was any impact on tumor seeding.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, numerous studies have also revealed that miR‐141‐3p exerts regulatory role in tumorgenesis and progression by serving as an oncogene. For example, exosomal miR‐141‐3p promotes the bone metastasis of prostate cancer through modulating osteoblast activity (Ye et al, ). Similarly, another study also confirmed that miR‐141‐3p was aberrantly upregulated in ESSC and subsequently promoted cancer progression and metastasis through activating AKT/PI3K pathway (Ishibashi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that secreted miR‐141‐3p reduced levels of DLC1 in osteoblasts and activated the p38MAPK pathway, promoting osteoblast proliferation and OPG/RANKL expression. In addition, they also found that EVs derived from PCa had bone‐target specificity and promoted osteoblastic bone metastasis in vivo . Karlsson et al .…”
Section: Therapeutic Strategies For Urological Cancer Using Evsmentioning
confidence: 96%
“…In addition, they also found that EVs derived from PCa had bone-target specificity and promoted osteoblastic bone metastasis in vivo. 111 Karlsson et al reported that EVs derived from the murine PCa cell line, TRAMP-C1, decreased fusion and differentiation of murine osteoclast precursors to mature multinucleated osteoclasts. Although the molecular mechanism underlying this phenotype was not shown, they suggested that EVs derived from PCa also regulated osteoclast differentiation in bone metastatic sites.…”
Section: Prostate Cancer (Pca)mentioning
confidence: 99%